Medically Documenting Disability in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) Cases - Comerford, Barbara B.; Podell, Richard (Frontiers in Pediatrics, 2019)
Patients with severe myalgic encephalomyelitis/Chronic fatigue syndrome (ME/CFS) experience debilitating physical and cognitive symptoms, which often result in the need to file disability claims. A significant number of ME/CFS patients are children or adolescents. ME/CFS patients often turn to physicians who are not trained to recognize and diagnose ME/CFS, and who might or might not understand that ME/CFS is a multi-system primarily physical illness. Such misperceptions can adversely affect the doctor-patient relationship, the clinical outcomes, as well as the results of disability claims